The Dictionary as Inventory: Notes on Luis Da Câmara Cascudo's Dicionário Do Folclore Brasileiro - Fernández Bravo, Álvaro (2008)
The dictionary can be thought of as a book of an instrumental kind, a tool for pragmatic and utilitarian knowledge. Useful for translating, understanding, communicating and deciphering an unknown code, it serves as a bridge between different languages and cultures. Even when the dictionary operates inside a culture as an educational device, it intercedes between a curious reader and an established body of knowledge, translating and explaining, showing and teaching. The dictionary illuminates an unknown area of knowledge. In this text I propose to question the norms associated with the typical distinctions made between monolingual and bilingual dictionaries. All dictionaries, I contend, connect dissimilar universes. From the moment they begin to organize a mass of concepts, submitting them to an external order (be it alphabetical or other), they impose upon a set of previously foreign meanings their own distinctive shape. In the dictionary there is always a relationship between dissimilar territories: between the oral and written, between popular culture and learned culture, between an unorganized body and the linguistic order that articulates it, between the etymology of a word (its historical meaning) and its contemporary usage. As with encyclopedias, and probably to an even more radical degree, dictionaries are not "read" in the traditional sense. The dictionary is an "unreadable" book; it is merely "used", accessed, employed in a fragmentary and conjunctural way. As they say in English: 'you might as well read the phone book'. Like a phone book, the dictionary is lacking in plot; rather, it is a list articulated by an alphabetical order. So what purpose does a dictionary serve? What does it contain? Why does it continually accumulate and under what criteria does it gather the linguistic and semantic legacy contained within its pages? What is the constructive principle that articulates its collection? Where is its inventory inscribed: in the nation, on the common tongue, in some pre-national or trans-national culture, or in the repository of universal knowledge? What is the relationship between the dictionary and the nation? What concepts, things, intangible heritages or material cultures become attached, connected, compared and translated by the dictionary?All these questions are quite applicable to the works of Luís da Câmara Cascudo, and I hope you will allow me to use them throughout these pages to develop an hypothesis about dictionaries and inventories. The Dicionário do Folclore Brasileiro was published as a result of an initiative by Augusto Meyer in 1943, who from the Instituto Nacional do Livro conceived it as part of the Brazilian Encyclopedia whose master plan was written by Mário de Andrade. The book is considered a synthesis of Cascudo?s vast work. I am interested in Cascudo?s work because of the principles on which it was built, the inventory that it gathers, and because it allows us to deduce something that does not appear in any list: the logic of a culture, its axiomatic regime, where it places value, what it chooses to remember, and which entries ('verbetes') are ultimately worthy of being submitted to the order of the inventory.  What the dictionary stores (and what it forgets) translates to what is valued in a historic and cultural conjuncture.